Voluntary Motivation and Emotional Well-being: Exploring Differences Based on Internal and External Drives - Vitrianingsih, Yeni; Issalillah, Fayola (Journal of Social Science Studies, 2021)
This research aims to explore how individuals’ motivations for volunteering can affect their emotional well-being. Voluntary motivations driven by internal needs, such as the desire to benefit others or the search for meaning in life, often have a more significant positive impact on individual happiness. External motivations, such as the drive for social recognition or external rewards, do not always result in long-term improvements in well-being. Existing literature suggests that individuals who engage in internally motivated volunteering report more sustained satisfaction and well-being. While internal motivation is more often associated with higher happiness, social factors and the type of volunteering also influence its impact on emotional well-being. This research suggests that to maximize the benefits of volunteering, individuals should engage with motivations derived from their internal values, as well as engage in activities that support the development of healthy social relationships. The results of this study are expected to provide insights in designing more effective volunteering activities to improve participants well-being.